Dynamics of Urban Heat Island and Anthropogenic Emissions in Bekasi before and during COVID-19 Pandemic using Landsat 8 and Sentinel-5P - Parhusip, Ramanatalia; Shidiq, Iqbal Putut Ash; Semedi, Jarot Mulyo (Journal of Information Technology and Computer Science, 2022)
The rise in temperature in urban areas resulting in UHI formation is thought to be significantly driven by anthropogenic emissions due to human activities. During the COVID-19 pandemic, the Indonesian government issued the Large-Scale Social Restrictions (PSBB) and Community Activities Restrictions Enforcement (PPKM) policy. Bekasi Regency is part of the Jabodetabek megapolitan that applied strict PSBB and PPKM treatment during the pandemic. The decreasing industrial activity and traffic volume are expected to reduce air pollutants and thermal radiation. The research method uses processed satellite imagery from Sentinel 5P to get anthropogenic emissions concentrations (NO2 and SO2) and Landsat 8 to get land surface temperature (LST). The results showed that Bekasi had a slight decrease in the concentration of anthropogenic emissions during COVID-19 pandemic 2020, then increased during COVID-19 pandemic 2021. The areas affected by urban heat islands increased steadily during the COVID-19 pandemic. Therefore, when the concentration of anthropogenic emissions rises, the UHI ascends.